1994
DOI: 10.1021/np50104a020
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Constituents of Formosan Rubia akane

Abstract: A known steroid, in addition to triterpenoids, anthraquinones, naphthalenes and a new anthraquinone glycoside, xanthopurpurin 3-O-beta-D-glucoside, were isolated from the roots of Rubia akane grown in Taiwan. Mollugin, a naphthohydroquinone, showed strong inhibition of arachidonic acid (AA)-induced and collagen-induced platelet aggregation. In contrast, 2-methyl-1,3,6-trihydroxyl-9,10-anthraquinone, xanthopurpurin 3-O-beta-D-glucoside, and xanthopurpurin showed mainly strong inhibition of collagen-induced plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 7 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…Anthraquinone, anthraquinone glycoside, naphthoquinone, naphthoquinone glycoside, furomollugin, mollugin, alizarin, lucidin pimeveroside, ruberythric acid, purpurin, xanthopurpurin, cyclohexapeptide, alkaloid and lignan have been reported from Rubia species. [1][2][3][4] In the course of screening tests for topoisomerase I and II inhibitors and cytotoxicity of 40 species of Korean traditional anticancer plants, we found that the methylene chloride fraction from the roots of Rubia cordifolia L. (the methanol extract of this root was subsequently fractionated into four fractions; methylene chloride, ethyl acetate, n-butanol and water) showed strong cytotoxicity against HT-29 and MCF-7 cell lines, as well as DNA topoisomerase I and II inhibitory activities. In our previous studies of the methylene chloride fraction of this plant, we isolated seven compounds belonging to the lignan, anthraquinone, triterpenoid and sterol groups.…”
mentioning
confidence: 99%
“…Anthraquinone, anthraquinone glycoside, naphthoquinone, naphthoquinone glycoside, furomollugin, mollugin, alizarin, lucidin pimeveroside, ruberythric acid, purpurin, xanthopurpurin, cyclohexapeptide, alkaloid and lignan have been reported from Rubia species. [1][2][3][4] In the course of screening tests for topoisomerase I and II inhibitors and cytotoxicity of 40 species of Korean traditional anticancer plants, we found that the methylene chloride fraction from the roots of Rubia cordifolia L. (the methanol extract of this root was subsequently fractionated into four fractions; methylene chloride, ethyl acetate, n-butanol and water) showed strong cytotoxicity against HT-29 and MCF-7 cell lines, as well as DNA topoisomerase I and II inhibitory activities. In our previous studies of the methylene chloride fraction of this plant, we isolated seven compounds belonging to the lignan, anthraquinone, triterpenoid and sterol groups.…”
mentioning
confidence: 99%
“…Thus, it appears that R. cordifolia inhibits action of PAF at its receptor level either by blocking it or by desensitization [111]. Mollugin (69) showed strong inhibition of arachidonic acid (AA)-induced and collagen-induced platelet aggregation [112]. In contrast, 1,3,6-trihydroxyl-2-methyl-AQ (45), and xanthopurpurin (35) showed mainly strong inhibition of collageninduced platelet aggregation [112].…”
mentioning
confidence: 99%
“…, columns[3][4][5][6]. The results show that the majority of the compounds inhibited the tested microorganisms.…”
mentioning
confidence: 89%
“…1) [5]. They have also been isolated from Rubia cordifolia, which is used widely in traditional medicine to treat coughs, bladder and kidney stones, joint inflammation, uterine hemorrhage, and uteritis [6,7]. Recently, H H the structure and stereochemistry of these compounds were determined by X-ray crystallography, and the total synthesis of rubioncolin B (2) was accomplished by Traner [4].…”
Section: Introductionmentioning
confidence: 99%